1996
DOI: 10.1115/1.2836688
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Wake-Affected Heat Transfer Around the Circular Leading Edge of Blunt Body

Abstract: Detailed measurements are performed about time-averaged heat transfer distributions around the leading edge of a blunt body, which is affected by incoming periodic wakes from the upstream moving bars. The blunt body is a test model of a front portion of a turbine blade in gas turbines and consists of a semicircular cylindrical leading edge and a flat plate afterbody. A wide range of the steady and unsteady flow conditions are adopted as for the Reynolds number based on the diameter of the leading edge and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…1. This apparatus is almost the same with one used in previous heat transfer test by Funazaki (1996), except for the secondary air supply system. The main flow rate is adjusted by the inlet valve of the blower.…”
Section: Test Apparatus and Instrumentmentioning
confidence: 99%
See 3 more Smart Citations
“…1. This apparatus is almost the same with one used in previous heat transfer test by Funazaki (1996), except for the secondary air supply system. The main flow rate is adjusted by the inlet valve of the blower.…”
Section: Test Apparatus and Instrumentmentioning
confidence: 99%
“…Pressure distributions around the test model are obtained using the test model of the same dimensions with the present one except for cooling holes, as had been employed by Funazaki (1996). Local flow velocity t/ ]ocal is then determined from those data.…”
Section: Fig 3 Layout Of Thermocouples and Film Holes (Unfolded Surfmentioning
confidence: 99%
See 2 more Smart Citations
“…Magari and Lagraff [10] measured the heat transfer in the stagnation region of a cylinder over a range of Mach number, Reynolds number, and free-stream turbulence intensity. Funazaki [11] measured the time-averaged heat transfer distributions around the leading edge of a blunt body, under the influence of incoming periodic wakes. He found that the wakes passing over the leading edge cause a significant increase in heat transfer before flow separation.…”
Section: Introductionmentioning
confidence: 99%